Cardiac catheterization: The interview in front of the patient's wishes (Research, Society and Development, 2018)
Units that perform cardiac catheterization are sectors where the normal and pathological state of the cardiovascular system is studied, intervening when necessary by means of procedures. Thus, this study has the objective of knowing and evaluating how the interview is being performed in patients undergoing cardiac catheterization in a mid-size hospital in the interior of Rio Grande do Sul. This is an exploratory and descriptive study , with a qualitative approach, where 10 patients who underwent cardiac catheterization were interviewed at outpatient level. The age of study participants ranged from 44 to 79 years. This demonstrates that the mean age of patients requiring cardiac catheterization is in agreement with the mean. Studies have shown that the average age for catheterization depends on pre-existing factors, exposing almost 90% of the risk attributable to coronary disease that affects the population, being the main cause of death in the world. It was evident that the guidelines for the procedure are essential for patients and their families, since most of them are not aware of the procedure and are anxious about the procedure.